(untitled) (Global Journal of Science Frontier Research, 2015)
Our approach incorporates the effective stepwise CO 2 purification in the free atmosphere by spraying of alkaline compounds together with acoustic acting inside the cloud via an aircraft. The alkalis cause significantly increases of the CO 2 solubility in further rainy droplets during their gravitational fall to provide the effective carbon transport from under-cloud atmosphere to the ground. The second step proposes an acoustic influence where droplets are triggered inside clouds by sound waves for coalescence. Special acoustic generators are considered, also optimal regimes for cloud droplets have been found at low frequencies with necessary acoustical power. The proposed alkaline method can compensate for annual carbon emission by its application at 0.4% -0.1% at our planet surface.